Pseudomembranous colitis secondary to methicillin-resistant Staphylococcus aureus (MRSA) - Pressly, Kalynn B (BMJ Case Rep, 2016)
A 37-year-old woman with a history of type II diabetes and Crohn's disease, status postcholecystectomy, presented with a >2-week history of cramping abdominal pain, nausea, non-bloody/non-bilious emesis and, later, diarrhoea. A flexible sigmoidoscopy was performed, revealing that ‘a segmental pseudomembrane was found from rectum to sigmoid colon’. Clostridium difficile PCR on the stool was repeated twice and resulted negative both times. A food history prior to onset of symptoms was consistent with Staphylococcal food poisoning and a stool culture was positive for heavy growth of methicillin-resistant Staphylococcus aureus and the absence of enteric flora. The patient was successfully treated with oral vancomycin.